Legal Consequences For Companies For Violations Of Collective Bargaining Agreements - Rahmawati, Andiani Putri; Mahanani, Anajang Esri Edhi (Fakultas Hukum Universitas Widya Mataram, 2023)
ABSTRACT Collective Labor Agreements (PKB) made between companies and workers' unions must refer to the Law governing Manpower in Indonesia in order to guarantee workers' basic rights, guarantee equality and opportunity and treatment without discrimination for the welfare of workers. If the Collective Labor Agreement made is contrary to applicable laws, it can result in the Collective Labor Agreement being null and void by law. In this research, the writer wants to examine the Juridical Review of the Collective Labor Agreement between PT x and the Workers' Union y. The type of legal research in this thesis is normative legal research and uses qualitative data analysis methods. In the application of the Collective Labor Agreement (PKB) by PT x with the Labor Union y, there are several discrepancies between the contents of the clauses contained in the Collective Labor Agreement (PKB) and the provisions contained in the Law governing Manpower in Indonesia. Even though there are some discrepancies in the contents of the Collective Labor Agreement clause made between PT x and y. However, the substance and other components contained in the Collective Labor Agreement (PKB) are in accordance with the laws governing employment in Indonesia. Keywords: Collective Labor Agreement, workers, null and void